Development of a low cost anthropomorphic robotic hand driven by modified glove sensor and integrated with 3D animation - Ariyanto, Mochamad; Ismail, Rifky; Nurmiranto, Ahmad; Caesarendra, Wahyu; Paryanto; Franke, Jörg (IECBES 2016 - IEEE-EMBS Conference on Biomedical Engineering and Sciences, 2016)
In this paper, a low cost anthropomorphic robotic hand is developed using low cost materials. The robotic hand has 6 joints and 6 actuators. User or operator gives the hand movement command by a modified glove sensor. The glove consists of six flex sensors placed on the fingers and wrist join that detect the bend of the fingers into a joint angle in each finger. 3D CAD model of robotic hand is exported into SimMechanics model using SimMechanics link to generate SimMechanics block diagram that can run in MATLAB/ Simulink environment. The model in SimMechanics is utilized as 3D animation hand. The relationship of the servo motor rotation angle among metacarpal phalangeal (MCP), proximal inter phalangeal (PIP) and distal inter phalangeal (DIP) joints will be presented. Finally, the performance of robotic hand is tested to grasp various objects and to perform specific motion augmented with 3D animation. The experiment results show the successful development of a low cost anthropomorphic robotic hand that can perform activities of daily living (ADLs).
CRIS-Team Scopus Importer:2023-03-07
Keywords: 3D animation; anthropomorphic; flex sensor; robotic hand; SimMechanics